Eksistensi Topeng Rangda Gaya Singapadu - Adesastrawiguna, Iputu; Mudra, I Wayan; Muka, I Ketut (Hastagina : Jurnal Kriya Seni, 2025)
In the implementation of the Merdeka Belajar Kampus Merdeka program for the even semester, students took a research program on the Singapadu style Rangda mask. This opportunity was used to explore and understand the Rangda mask in Singapadu, both in terms of history, the manufacturing process, and the form and philosophical meaning of the Singapadu style Rangda mask. In its development, there are still many artists in Singapadu and outside Singapadu who do not know the real history of the Singapadu style Rangda mask. The ignorance and understanding of today's young generation about the history of the Singapadu style Rangda mask is an interesting thing to be studied further. In addition to studying the history of the existence of the Rangda mask Singapadu, also researches the process, form and meaning of philosophy. The method used is a qualitative research method and emphasizes qualitative descriptive analysis. The data collection method used For do study This is method observation, interview in a way in-depth, documentation and study literature. In addition, research This use four method research data analysis qualitative that is method data collection, data reduction, data presentation, and data extraction conclusion. This study uses a historical approach that aims to find out information related to the historical traces of the Singapadu style Rangda mask. The implementation of research on the Existence of the Singapadu Style Rangda Mask resulted in findings related to history, the manufacturing process, and knowing the form and philosophical meaning of the Singapadu style Rangda mask.